Educational Financing and Administrative Governance Effectiveness in Islamic Schools - Ahmad Fawaiz Hakim; M. Al Aden Faqih; Syahrul Fauzi Muharom; Siti Anisah; Muhamad Rizza (ISLAMIKA, 2026)
Despite the critical role of educational financing in institutional sustainability, limited research has examined how financing management affects the effectiveness of administrative governance in Islamic schools. This study aims to analyze the effect of educational financing management on administrative governance effectiveness at MA Darul Ihya Ciomas Bogor, Indonesia. A quantitative correlational design was employed using simple linear regression. The study involved 35 teachers and administrative staff selected through saturated sampling. Data were collected through structured Likert-scale questionnaires and analyzed using SPSS version 25 through descriptive statistics, reliability testing, normality testing, Pearson correlation, and regression analysis. The findings show a high level of educational financing management (M = 33.31) and a moderate-to-high level of administrative governance effectiveness (M = 30.97). The results also indicate a strong positive correlation between educational financing management and administrative governance effectiveness (r = 0.753, p < 0.001). Regression analysis confirms that educational financing management significantly influences administrative governance effectiveness (R² = 0.568; β = 1.413), explaining 56.8% of the variance. The study concludes that effective educational financing management strengthens administrative governance in Islamic schools, particularly through improved budgeting, transparency, and financial accountability. These findings contribute to educational management theory by extending empirical evidence on the relationship between financing practices and governance effectiveness in Islamic educational institutions. Practically, the study highlights the need for madrasah administrators and policymakers to improve budget planning, financial transparency, and digital integration in administrative systems. Future research should examine additional variables, such as leadership and technology, using larger samples and broader institutional contexts.